Joint polarizations of W pair production at the LHC at NLO QCD+EW accuracy - Dao, Thi Nhung; Le, Duc Ninh (Communications in Physics, 2025)
In this contribution, we present new results of next-to-leading order (NLO) electroweak corrections to the doubly polarized \(W^+W^-\) production cross sections at the LHC, via the full leptonic final state. This calculation has been recently achieved independently by two groups: one in Germany and our group in Vietnam. A comparison of the two results will be presented. We include also the NLO QCD corrections in the numerical analysis since they are dominant and therefore important for comparison with experimental results.